2016
DOI: 10.1039/c5gc02157j
|View full text |Cite
|
Sign up to set email alerts
|

Combining bio- and chemo-catalysis for the conversion of bio-renewable alcohols: homogeneous iridium catalysed hydrogen transfer initiated dehydration of 1,3-propanediol to aldehydes

Abstract: Abstract.Combining whole cell biocatalysis and chemocatalysis in a single reaction sequence avoids unnecessary separations, and the associated waste and energy consumption. Bacterial fermentation has been employed to convert waste glycerol from biodiesel production into 1,3-propanediol. This 1,3-propanediol can be extracted selectively from the aqueous fermentation broth using ionic liquids. 1,3-propanediol in ionic liquid solution was converted to propionaldehyde by hydrogen transfer initiated dehydration (HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 63 publications
1
30
0
Order By: Relevance
“…The substrate and internal standard CH 3 OH solutions for calibration were prepared and then analysed by GC/MS spectroscopy according to the method that this group recently reported, 14 leading to the following calibration curve: y = 0.4449x  0.0345 (R 2 = 0.9938) (x = C 5 /C 6 , y = A 5 /A 6 ). (Eq.…”
Section: Analysis Of Reaction Product Solutions Of Htid Of 13-pdo Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The substrate and internal standard CH 3 OH solutions for calibration were prepared and then analysed by GC/MS spectroscopy according to the method that this group recently reported, 14 leading to the following calibration curve: y = 0.4449x  0.0345 (R 2 = 0.9938) (x = C 5 /C 6 , y = A 5 /A 6 ). (Eq.…”
Section: Analysis Of Reaction Product Solutions Of Htid Of 13-pdo Inmentioning
confidence: 99%
“…13 Further investigations revealed that, in the absence of amine dehydration could be affected to yield propionaldehyde as the major product. 14 This occurs due to dehydrogenation of 1,3-PDO, which yields an aldol that rapidly dehydrates to acrolein and is then hydrogenated to propionaldehyde. This is a Hydrogen Transfer Initiated Dehydration (HTID) reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Glycerol, with three functional hydroxyl groups, allows various selective catalytic transformations to chemicals (e.g. acrolein, acrylic acid, propanediol and lactic acid). Notably, glycerol selective oxidation to lactic acid has received growing attention, because it supports a new chemical route for large‐scale lactic acid production.…”
Section: Introductionmentioning
confidence: 99%
“…In imidazolium IL [C2mmim][NTf2] at 150 ºC C2 10 was found to have a better tolerance for KOH than C1. 9 Trifluorinated benzyl Cp*Ir(III)NHC complex C2 was chosen as the catalyst for the HTID reaction of 1,3-propanediol using BILGs. The surface area of the material was found to increase as the proportion of phosphonium IL was increased from G1 to G2.…”
Section: Htid Catalytic Conditionsmentioning
confidence: 99%
“…HTID reactions were performed by a modification of the procedure detailed in our literature. 9,10 1,3-Propanediol (1.25 g, 0.0164 mol), C2 (0.135 g, 0.236 mmol), [P6,6,6,14][OH] SiO2 gel G1, G2 or G3 (for quantities see Table S6), and [C2mmim][NTf2] (2.9 g, 0.0071 mol) were mixed in a 50 mL round bottom flask connected, through a distillation condenser, to a 50 mL glass tube. The mixture was maintained at 150 °C, at a controlled pressure of ca.…”
Section: Htid Of 13-pdo Using Mixed [C4mmim][ntf 2 ]/[P66614][oh]mentioning
confidence: 99%